A execução orçamentária e financeira da UFSM: uma análise via mapeamento de processo e mensuração dos custos dos materiais de consumo e bens permanentes - Paines, André de Toledo (2018)
The present paper promoted a study at Federal University of Santa Maria (UFSM), which consisted of identifying, describing and mapping the budget and financial implementation process of consumer materials and permanent assets at the institution, as well as in the measurement of the costs of executing this process, in order to verify the possibility of optimizing the use of its resources. Because this is a study carried out in a public organization, we first present concepts about these organizations, as well as the institution in question, UFSM. Next, we present researches on the methodologies used in the processes mapping and costing in the public service, defining the most appropriate, and adapting it to the reality of the object of study. For the accomplishment of the work, a qualitative research was carried out, with a descriptive research. The data were obtained through interviews with the servers responsible for the execution of the processes tasks, in order to obtain a detailed description of the tasks performed during it. In addition, research was done on documents and on the budget and financial execution systems of the institution, in order to get an idea of the costs involved in the steps of the chosen process. The process mapping was done using Bizagi Modeler, a freeware processes management tool that allows the creation of many types of diagrams, using BPMN 2.0 notation. From the results obtained in the mapping, a new methodology was proposed to execute the process, with suggestions for improvements that impact both costs and speed of process. It should be noted that the main problems are the printing of unnecessary documents and the existence of redundant tasks. In this way, it was suggested a redesign of the structures of some sectors responsible for the process, as well as not printing about 90% of the original digital documents generated during its execution, which would make it faster and less costly for the Institution.